The new normal: What does maths and stats support and teaching look like post pandemic? - Pawley, Susan; Neate, Andrew (MSOR Connections, 2024)
The workshop “The new normal: What does maths and stats support and teaching look like post pandemic?” took place on the 1st of December 2022 and discussed the changes to mathematics and statistics support since the lifting of restrictions after the pandemic. The event consisted of five short talks where presenters explored the changes that had occurred to mathematics and statistics support at their institutions and concluded with a discussion on how to effectively combine online and face-to-face support and how to increase engagement in all forms of support. This report summarises the talks and discussion, concluding with some thoughts on the changes still required and how we can support each other.